Mechanical licensing of the NLRP3 inflammasome in hypertensive vasculature: Integrin mechanotransduction and cytoskeletal control of vascular inflammation - Noof Abdulrahman Alrabiah; Safwan Abid Al-hameed Suliman; Lashin S. Ali; Waseem Ali Hasan; Amany Said Sallam; Rabab S. Hamad; Etedal Ahmed A. Ibrahim; Eman Hamza; Nesreen Elsayed Morsy; Ahmed Shata; Hanan Eissa; Alshaimaa A. Farrag; et al. (Tissue and Cell, 2027)

BD1-biased BET inhibition attenuates TXNIP-associated inflammation in diabetic MASH - Rabab S. Hamad; Sameh Saber; Elsayed A. Elmorsy; Maha M. Amer; Mohamed A.M. Ali; Hanan Eissa; Alshaimaa A. Farrag; Norhan Ahmed AbuoHashish; Shereen hamed; Mahmoud A. Abdelaziz; Adel I. Alalawy; Alaa Muqbil Alsirhani; et al. (Tissue and Cell, 2027)

CD38-driven NAD⁺ depletion governs crypt structure and barrier dysfunction in fluorouracil-induced colonic mucositis: From metabolic collapse to architectural remodeling - Elsayed A. Elmorsy; Rabab S. Hamad; Mohammed Alorini; Attia M. Gabr; Hamad Alsaykhan; Mostafa M. Khodeir; Mohamed F. Hindawy; Abdulaziz A. Alsalloom; Eman Mohamad El Nashar; Ahmed G. Hamad; Haytham Ali; Mohammed Ashraf Ali; et al. (Tissue and Cell, 2026)

Interrupting a mitochondrial DNA–driven innate immune circuit attenuates hepatic tissue remodeling and fibrotic architecture in experimental steatohepatitis - Rabab S. Hamad; Sura Akram Mohammed; Waseem Ali Hasan; Norhan Ahmed AbuoHashish; Sherin Refat El Afify; Mohamed A.M. Ali; Alaa Eldin Ahmed Mohamed; Attalla F. El-kott; Mohammed A. AlShehri; Kareem Morsy; Alshaimaa A. Farrag; Karem Mohamed Salem; et al. (Tissue and Cell, 2026)

Engineering stem cell morphology and tissue architecture through nano-engineered materials - Rabab S. Hamad; Sameh Saber; Elsayed A. Elmorsy; Alshaimaa A. Farrag; Hanan Eissa; Eman Mohamad El Nashar; Norah Saeed Al-Zahrani; Areej M. Alshehri; Mohamed A.M. Ali; Maha M. Amer; Mohamed R. Abdel-Hamed; Enas A. Mohamed; et al. (Tissue and Cell, 2026)

STING organelle stress sensing in the liver drives hepatocyte fate and remodeling - Rabab S. Hamad; Elsayed A. Elmorsy; Fatma Elnaghy; Maha M. Amer; Mohamed R. Abdel-Hamed; Alshaimaa A. Farrag; Hanan Eissa; Attalla F. El-kott; Sally Negm; Mohammed A. AlShehri; Mohamed A.M. Ali; Anis Ahmad Chaudhary; et al. (Tissue and Cell, 2026)

Ultrastructural organization of the neurovascular unit: Nanoscale perspectives on blood-brain barrier architecture - Rabab S. Hamad; Sameh Saber; Alshaimaa A. Farrag; Hanan Eissa; Elsayed A. Elmorsy; Attalla F. El-kott; Mohammed A. AlShehri; Eman A. Al-Shahari; Waleed Eltantawy; Mohamed A.M. Ali; Anis Ahmad Chaudhary; Ahmed Gaafar; et al. (Tissue and Cell, 2026)

L-tryptophan functionalized NH2 -UiO-66(Zr) crosslinked with glutaraldehyde adsorbent for sensitive detection and effective removal of mercury (II) - Nadia H. Elsayed; Nawaa Ali H. Alshammari; Maymounah N. Alharthi; Raedah A.S. Alatawi; Abeer Abdulaziz H. Bukhari; Ali Hamzah Alessa; Menier Al-Anazi; M.A.M. El-Afify (Journal of Water Process Engineering, 2026)

Multi-objective optimization of ultrasound-assisted hybrid drying to preserve rapeseed oil and protein - Khaled Abdeen Mousa Ali; Changyou Li; Mengyao Chen; Zhurong Chen; Zhanhong Huang; Marwa Abd-Elnaby Mohammed; Elsayed Ragab Shousha; Ye Zhang (Journal of Stored Products Research, 2026)

Biological effects of statins in systemic sclerosis: a systematic review and meta-analysis of 323 patients - Mostafa A. Khalifa; Hamzah M. Alghzawi; Shehabeldin S. Anan; Ahmad Al Rifai; Ayah A. Anwar; Hayder Ali Raheem Al-Saedi; Eman Awady; Islam Masood; Mohamed Elsayed Badr; Mohamed Ismail; Obada Muayaid; Omar M. Ahmed; et al. (DARU Journal of Pharmaceutical Sciences, 2026)

Statistical optimization of extracellular antimicrobial metabolite production by Streptomyces enissocaesilis ASB isolate targeting multidrug-resistant pathogens - Ahmed S. Badawy; Esmail M. El-Fakharany; Jehan S. Albrahim; Elsayed K. Bakhiet; Salah G. Ali; Ahmed K. Saleh; Hamada El-Gendi (Biologia, 2026)

“Protective antiseptic efficacy of Allolobophora caliginosa coelomic fluid in a mouse model of sepsis induced by faecal slurry” - Marwa Ahmed Abdelfattah; Ayman Saber Mohamed; Manar Abd Elhalem; Nour Elsadek; Seif Eldin Mohamed; Sara Osama; Alia Baher Samir; Halla Ahmed Elsayed; Farha Youssef Abdullah; Sohair R. Fahmy; Sara Bayoumi Ali (Tissue and Cell, 2026)

Breaking a mitochondrial danger–STING feed-forward amplifier preserves alveolar–capillary architecture and dampens interferon–chemokine signaling in acute lung injury - Elsayed A. Elmorsy; Maha M. Amer; Rabab S. Hamad; Mohamed R. Abdel-Hamed; Alshaimaa A. Farrag; Mohammed Alorini; Mostafa M. Khodeir; Mohamed A.M. Ali; Ahmad H. Alhowail; Enas A. Mohamed; Abdulaziz A. Alsalloom; Hamad Alsaykhan; et al. (Tissue and Cell, 2026)

Corrigendum to : The nano–biointerface as a structural regulator of cell behavior: Interactions of extracellular vesicles, synthetic nanocarriers, and nanofibers with cells [Tissue Cell, Vol. 101, August 2026, 103431] - Rabab S. Hamad; Sameh Saber; Alshaimaa A. Farrag; Hanan Eissa; Elsayed A. Elmorsy; Attalla F. El-kott; Mohammed A. AlShehri; Eman A. Al-Shahari; Waleed Eltantawy; Mohamed A.M. Ali; Anis Ahmad Chaudhary; Ahmed Gaafar; et al. (Tissue and Cell, 2026)

The nano–biointerface as a structural regulator of cell behavior: Interactions of extracellular vesicles, synthetic nanocarriers, and nanofibers with cells - Rabab S. Hamad; Sameh Saber; Alshaimaa A. Farrag; Hanan Eissa; Elsayed A. Elmorsy; Attalla F. El-kott; Mohammed A. AlShehri; Eman A. Al-Shahari; Waleed Eltantawy; Mohamed A.M. Ali; Anis Ahmad Chaudhary; Ahmed Gaafar; et al. (Tissue and Cell, 2026)

Seaweed Liquid Extract Improves Growth, Immunity, and Gene Expression in Nile Tilapia (Oreochromis niloticus) - Mohamed Ashour; Einar Ringø; Fawzia S. Ali; Ahmed Mamoon; Othman F. Abdelzaher; Roshmon Thomas Mathew; Abdallah Tageldein Mansour; Yousef Ahmed Alkhamis; Elsayed S. I. Mohammed; Hesham S. Hassanien; Mohamed A. Elokaby; Mohamed M. Mabrouk (Journal of Applied Phycology, 2026)

Effect of Beet Molasses Application On Wheat (Triticum aestivum L.) Germination and Seedling Growth Under Salinity Stress - Hossam S. El-Beltagi; Mohamed Fathi El-Nady; Adel A. Rezk; Metwaly Mahfouz Salem Metwaly; Hosny H. Kesba; Rania Anwar Khedr; Mohamed M. El-Mogy; Elsayed Abd Elmaksoud Abomarzokae; Wael Elmenofy; Khloud Ali Hamza (Journal of Crop Health, 2026)

Combined Bacillus Amyloliquefaciens and Bacillus Licheniformis for Preventive Health Management: Effects on Growth Performance, Intestinal Integrity, and Oxidative Status in Broilers Under Controlled Housing - Ahmed Ali Saleh; Mahmoud M. Aboud; Neamat Badwi; Mohammed A. Kamal; Elsayed Osman Hussein; Branislav Galik; Hana Hakami; Ahmed Sami; Abeer A. Kirrella (Probiotics and Antimicrobial Proteins, 2026)

Adenosine A₂A receptor as a dual-acting molecular switch: Glial morphological changes and neurovascular tissue remodeling in neuroinflammation and neurodegeneration - Heba Ibrahim Abd El-Moaty; Ahmed Sameh; Sameh Saber; Rabab S. Hamad; Elsayed A. Elmorsy; Norah Suliman Alsoqih; Alshaimaa A. Farrag; Hanan Eissa; Attalla F. El-kott; Sally Negm; Mohammed A. AlShehri; Mohamed A.M. Ali; et al. (Tissue and Cell, 2026)

FOXO3a-mediated structural and cellular remodeling in liver tissue: Implications for apoptosis and homeostasis - Heba Ibrahim Abd El-Moaty; Sameh Saber; Rabab S. Hamad; Elsayed A. Elmorsy; Alshaimaa A. Farrag; Simona Cavalu; Hanan Eissa; Attalla F. El-kott; Sally Negm; Mohammed A. AlShehri; Mohamed A.M. Ali; Waseem Ali Hasan; et al. (Tissue and Cell, 2026)

Mechanistic insights into sulfate-driven performance adaptation and membrane fouling in a UASB-SBR-AXMBR system: metabolic network reconstruction and microbial community succession - Zhengwang Wu; Antong Duan; Yangkai Liu; Ruihui Chen; Mohd Fadhil Md Din; Eli Hendrik Sanjaya; Elsayed Ali Elsayed Ali; AbdelGawad Saad; Zhihua Liu; Hong Chen (Environmental Research, 2026)

Impact of nano-selenium supplementation on in vitro gas production, methane mitigation, and in vivo performance of Ossimi Egyptian Sheep - Hamdy Mohamed Khattab; Ahmed Zaki El-Basiony; Salwa Mahmoud Hamdy; Mahmoud Hassan; Nasr Elsayed El-Bordeny; Osama Mohamed Darwesh; Gamal Ali Elsayaad; Raafat Mahmoud Mohamed Gomaa (Tropical Animal Health and Production, 2026)

Insights into performance degradation of roof runoff treatment in field-scale bioretention facilities packed with zeolite and volcanic rock over three years of continuous operation - Jiakai Hu; Ronghua Xu; Jingyi Jiang; Muhammad Rizwan; Mohd Fadhil Md Din; Elsayed Ali Elsayed Ali; Eli Hendrik Sanjaya; AbdelGawad Saad; Zhe Kong; Hong Chen (Journal of Environmental Chemical Engineering, 2026)

Nitrogen removal performance responses to substrate concentration gradients in a vertical flow screening internal circulation bioreactor - Wang Binquan; Xiong Xiaoting; Yang Risen; Jin Jiao; Eli Hendrik Sanjaya; Mohd Fadhil Md Din; AbdelGawad Saad; Elsayed A.E. Ali; Chen Hong (Journal of Environmental Chemical Engineering, 2026)

Microbial decontamination and enhanced extraction of value-added compounds from Spirulina platensis using gamma radiation - Hamdy Elsayed Ahmed Ali; Mohamed S. Abd El-AL; Marwa M. Moussa; Ola M. Gomaa; Kamal A. Hassan; Eman A. El-fayoumy (World Journal of Microbiology and Biotechnology, 2026)
Spirulina platensis has garnered increasing attention as a valuable source of proteins, lipids, and pigments, with applications in the food, feed, and nutraceutical industries. However, large-scale cultivation in open pond systems is liable to microbial contamination, posing risks to product quality and productivity. This study evaluated the effects of gamma (γ) irradiation up to 10 kilogray (kGy) as a dual strategy for microbial decontamination and enhanced extraction of bioactive compounds from dried Spirulina powder. A dose of 4 kGy resulted in a substantial reduction in microbial populations, while irradiation at 6 kGy reduced microbial counts to levels below the detection limit of the applied culture-based methods, indicating effective decontamination. The D₁₀-values obtained for Bacillus sp. (0.44 kGy), Staphylococcus aureus (0.41 kGy), and Pseudomonas aeruginosa (0.58 kGy) demonstrate species-dependent radiosensitivity. Analyses using electron spin resonance (ESR), UV–Vis spectroscopy, Fourier transform infrared spectroscopy (FTIR), and lipid peroxidation assays demonstrated that γ-irradiation preserved the structural integrity of key biomolecules. Biomass irradiated at 6 kGy exhibited the highest recovery of lipid (60.83 ± 1.38 mg g⁻¹), protein (547.43 ± 2.97 mg g⁻¹), and carbohydrates (275.60 ± 2.50 mg g⁻¹). Pigment extraction also increased, yielding elevated levels of chlorophyll a (11.40 ± 0.10 mg g⁻¹), carotenoids (3.48 ± 0.30 mg g⁻¹), and phycobiliprotein (125.20 ± 0.70 mg g⁻¹). Antioxidant activity peaked at 69.61 ± 1.47% at the same dose, associated with enhanced phenolic content. Overall, γ-irradiation represents a promising biotechnological tool for producing microbiologically safe Spirulina biomass while improving the extraction of value-added bioactive compounds for nutraceutical and pharmaceutical applications.

Sustainable management of olive trees under saline irrigation and soil conditions using micro-irrigation systems and remote sensing - Mohamed M. Mahmoud; Mohamed E. Abuarab; Ayman Shaban; Ibrahim Hmmam; Asmaa Gamal Abd El-hamied; Amr Mossad; Ali Mokhtar; Elsayed Youssief Ghoniem (Irrigation Science, 2026)
The study was carried out to examine the sustainable management of irrigation water for olive cultivation in sandy soils with varying levels of water salinity at a farm situated in the Regwa region of EL-Beheira Governorate, Egypt, which is noted for its arid climate, aiming to improve the effective utilization of sustainable ecosystems while optimizing economic returns for agricultural producers. Field experiments were implemented over two successive growing seasons, specifically 2022–2023 and 2023–2024, employing seven distinct irrigation methodologies: micro-sprinklers, T-tape GR drippers, Root Zone Watering System (RZWS), inline drippers, inline PC drippers, mist sprayers, and bubblers. In the 2022–2023 season, the inline dripper treatment yielded the highest output of 13.78 ton ha −1 , followed by the inline PC dripper and micro-sprinkler systems, which yielded 13.20 ton ha −1 and 12.45 ton ha −1 , respectively. In contrast, the mist sprayer treatment produced the lowest yield at 7.61 ton ha −1 . The oil content in olive fruits reached optimal levels under bubbler and inline PC dripper treatments in the second growing season at 40.0% and 39.87%, respectively. Conversely, the minimum oil content was recorded under micro-sprinkler and inline dripper treatments in the first growing season, yielding 34.31% and 34.36%, respectively. During the first growing season, the inline dripper exhibited irrigation water productivities (IWPs) of 31.60 kg m −3 , followed by the inline PC dripper with an IWP of 30.28 kg m −3 . In stark contrast, the mist sprayer reported the lowest IWPs of 0.74 kg m −3 in the second growing season. The distribution patterns of soil moisture and salinity within the root zone were analyzed utilizing Surfer software. The most significant net farm income (NFI) was attained under the inline PC dripper treatment, with an NFI of 38,664.35 US$ y −1 , succeeded by the inline dripper and micro-sprinkler treatments with NFIs of 36,010.95 and 30,265.94 US$ y −1 , respectively; the mist sprayer demonstrated the lowest NFI at 17,186.49 US$ y −1 .

Pimenta racemosa extract ameliorates chemically induced ulcerative colitis in rats by suppressing inflammation and oxidative stress - Haitham A. Ibrahim; Fathia S. Elshaarawy; Mohamed I. S. Abd-elhady; Wafaa Hamdy; Merhan E. Ali; Asmaa A. Ahmed; Elsayed K. El-Sayed (Inflammopharmacology, 2026)
Pimenta racemosa ( P. racemosa ) tree leaves are used in traditional medicine to alleviate flatulence and gastrointestinal disorders. Ulcerative colitis (UC) is a gastrointestinal inflammatory disease with well-known inflammatory and immunoregulatory pathological features. The complexity of the disease requires multi-targeted treatment. Because of their relative safety and effectiveness, natural products can be utilized as adjunct and alternative agents to conventional UC treatment. So , the present work aimed to isolate phenolic constituents of the plant’s 80% aqueous methanol extract (AME) and evaluate its protective effect on acetic acid-induced ulcerative colitis (UC) in rats. The defatted AME was chromatographed, and structures of the isolated compounds were elucidated using UV, NMR spectroscopy and HPLC–ESI–MS analysis. Induction of ulcerative colitis was done using Acetic acid, the protective effect against ulcerative colitis was supported by histopathological and immunohistochemical examinations. The isolated compounds are Kaempferol 3- O - β -D-glucopyranoside (kaempferol 3- O -glucoside) or (Astragalin) (1) , quercetin 3- O-β -D-glucopyranoside (Isoquercetrin) (2) , Quercetin (3) , Catechin (4) , quercetin 3- O-α- L-rhamnospyranoside (Quercetrin) (5) . The AME of P. racemosa significantly alleviated the UC by decreasing the disease activity index and Wallace score. Additionally, GSH, CAT, and SOD were increased, and MDA was decreased, suggesting AME’s antioxidant activity. The decreased levels of WBCs, neutrophils, TNF-α, IL-1β, IL-6, MPO, and NF-κB p65 support the AME’s anti-inflammatory properties. The highest activity was recorded for the dose of 1000 mg/kg. These findings were in harmony with the histopathological examination and the Alcian Blue staining for mucin content. The current study revealed that the AME of P. racemosa has protective activities against UC in rats via its antioxidant and anti-inflammatory properties may be attributed to its phenolic profile.

Integrated hydroponics systems with anaerobic biogas slurry: Analysis of nitrified bio slurry, plant growth performance, and human health risk assessment - Tarek Mahrous; Ping Ai; Ali Abd-Elkader; Aibin Hu; Mahdy Elsayed (Bioresource Technology Reports, 2026)

A self-organized fuzzy neural model for the pressurizer system in nuclear power plants - Elsayed H. Ali; Amal A. Sheta; Sayed M. El-Araby; Mohammed I. Mahmoud; Tarek A. Mahmoud (Annals of Nuclear Energy, 2026)

Arbuscular mycorrhizal fungi confers resistance to Macrophomina phaseolina in coriander under different nitrogen fertilizer rates - Marzouk R. Abdel-Latif; Abdelrazek S. Abdelrhim; Ranya M. S. El-Ashmony; Yasmin M. R. Abdellatif; Hanaa A. H. Armanious; Ismail A. A. Tantawy; Mahmoud Elsayed; Abeer S. Alqurashi; Hatim M. Al-Yasi; Esmat F. Ali; Abdelmonim Ali Ahmad (Journal of Plant Pathology, 2026)

Exploitation of Sentinel-2 Spectral Bands and Vegetation Indices in Potato Yield Estimation - Mohamed E. S. Amin; Mohsen Nabil; Mahmoud. A. Abdelfattah; Elsayed. S. Mohamed; Ali G. Mahmoud (Journal of the Indian Society of Remote Sensing, 2026)

Evaluating the impact of quality control deficiencies on asphalt concrete mix performance - Ali Qabur; ElSayed Adel Fahmy; Ahmed M. Youssef; Magdy Shaheen; Mohammed Samir Eisa; Khaled Aati; Rouba Joumblat (Innovative Infrastructure Solutions, 2026)

Ferric Carboxymaltose Among Patients with Heart Failure and Iron Deficiency: An Updated Meta-Analysis of Randomized Controlled Trials - Ahmed Elmorsy Mohamed; Ahmed Farid Gadelmawla; Zeyad Kholeif; Elsayed Balbaa; Ameer Awashra; Mohamed Elnady; Ahmed Diaa; Mohab Elnashar; Haytham A. M. Dwaik; Eman Mohyeldin; Ranem Afify; Rana Rashwan; et al. (Cardiovascular Toxicology, 2026)

End-to-end deep SAE-DNN model for predicting Egyptian buffalo calf sex, weight, and daily milk yield - Sali Issa; Montaser Elsayed Ali; Qi Wang; Fatimah A. Al-Saeed; Mohamed Abdelrahman (Tropical Animal Health and Production, 2025)

Evaluation of lactoferrin administration as an antibiotic alternative growth promoter: impacts on rabbit’s growth, meat quality, blood biochemical parameters, immune status, antioxidant status, and tissue histology - Tharwat A. Imbabi; Shimaa A. Amer; Eman H. Halawa; Islam I. Sabeq; Abdel-Wahab A. Abdel-Warith; Elsayed M. Younis; Shimaa N. Edris; Simon J. Davies; Lamiaa M. El-Maghraby; Abdalla El-Hadary; Ebrahim Elkhtab; Mohamed H. Abdel Aal; et al. (Tropical Animal Health and Production, 2025)

The impacts of novel lyophilized milk fermented with potential probiotic Lactobacillus sp. on the physiological indicators, meat characteristics, blood parameters, and gene expression in weaned rabbits - Ebrahim Elkhtab; Ali Osman; Rania M. Y. Heakel; Elsayed M. Younis; Abdel-Wahab A. Abdel-Warith; Ahmed A. Aly; Mohamed H. Abdel Aal; Islam Sabeq; Shimaa A. Amer; Simon J. Davies; Tharwat A. Imbabi (Tropical Animal Health and Production, 2025)

Protamine sulphate for heparin reversal in percutaneous cardiac interventions: a systematic review and meta-analysis of randomized controlled trials - Elsayed Balbaa; Ahmed Farid Gadelmawla; Abdelrahman M. Tawfik; Ahmed Naeem; Ahmed Elbataa; Mohammad Bazzazeh; Ahmed Ramadan Fatiem; Khaled Ali; Obieda Altobaishat; Mohamed Abuelazm (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)
Vascular complications after percutaneous cardiac interventions are a significant cause of morbidity that affects post-procedural prognosis. Data about the efficacy and safety of routine protamine sulphate to prevent these complications remain scarce. Hence, we aim to assess the efficacy and safety of routine protamine sulphate use for heparin reversal in patients undergoing percutaneous cardiac interventions. We systematically searched PubMed, Embase, Cochrane, Scopus, and Web of Science for randomized controlled trials (RCTs) until September 2024. The RCTs’ quality was assessed using the Cochrane tool (RoB 2). Using R, we pooled dichotomous outcomes using risk ratios (RR) and continuous outcomes using mean differences (MD), both along the corresponding 95% Confidence interval (CI). PROSPERO ID: (CRD42024593002). Six RCTs with 1,076 patients were eligible. Hemostasis success was significantly higher in the protamine group (RR, 1.06; 95% CI [1.01–1.10]; P = 0.01), and the length of hospital stay was significantly shorter (MD, -0.46; 95% CI [-0.65, -0.26]; P < 0.01). There was no significant difference between both groups in stroke (RR, 0.60; 95% CI [0.18–2.03]; P = 0.41), major bleeding ( P = 0.25), minor bleeding ( P = 0.11), life-threatening bleeding ( P = 0.65), time to ambulation ( P = 0.13), all-cause mortality ( P = 0.92), hematoma/pseudoaneurysm ( P = 0.92), and major vascular complications ( P = 0.70). While protamine improved hemostasis success, its effect on reducing bleeding events and time to ambulation was insignificant. Also, reducing the length of hospital stay in the protamine group highlights its potential clinical benefit. Graphical Abstract

Reprogramming the hepatic immune microenvironment with mirtazapine in early neoplastic transformation: Evidence from a diethylnitrosamine-induced rat model - Elsayed A. Elmorsy; Sameh Saber; Ahmad H. Alhowail; Abousree T. Ellethy; Enas A. Mohamed; Hamad Alsaykhan; Hatim Y. Alharbi; Omar Almansour; Abdelrahman El-Sayed; Manal Mohamed Hatem; Ahmed Kaid Alantry; Walaa A. Allam; et al. (Chemico-Biological Interactions, 2025)

Sustainable valorization of agro-waste by microwave pyrolysis: mechanisms, optimization, catalyst pathways, integration strategies, and perspectives - Ahmed Elsayed Mahmoud Fodah; Haiping Yang; Xianhua Wang; Ziyue Tang; Rizk Rabea Kamel Elbessoumy; Mohamed Ahmed Shetawy; Elwan Ali Darwish; Taha Abdelfattah Mohammed Abdelwahab (Bioresource Technology, 2025)

Cardioprotective effects of ghrelin and Wharton’s jelly-derived mesenchymal stem cells, alone and in combination, in doxorubicin-induced myocardial injury in rats - Amy F. Boushra; Christina Sabry Yacoub; Hamed Mohamed Osman; Amani M. El Amin Ali; Azza Mohamed Elamir; Asmaa Mohamed Elsayed; Sarah Mahmoud Gamal (Journal of Molecular Histology, 2025)

Nutrient therapies: Boosting plant immunity for a sustainable future - Mohamed S. Attia; Amer M. Abdelaziz; Mostafa I. Abdelglil; Amr H. Hashem; Eslam K. Kandil; Eslam O. Elsawwah; Mohammed S. Helal; Salah M. Elsayed; Mustafa A. Nouh; Maryam M. Elsayed; Mohamed M. Ali; Mohamed Soliman Dora; et al. (Physiological and Molecular Plant Pathology, 2025)

Exogenous Zinc Alleviates Post-Anthesis Heat Stress by Improving the Defense Mechanism and Leaf Physiology of Bread Wheat - Muhammad Sarwar; Muhammad Farrukh Saleem; Aleena Anwar; Hassaan Ahmad; Basharat Ali; Muhammad Shahid; Abeer Hashem; Ajay Kumar; Elsayed Fathi Abd-Allah (Journal of Soil Science and Plant Nutrition, 2025)

Tailored ion-imprinted polymer for europium(III) recovery: A cellulose-based click chemistry approach - Nadia H. Elsayed; Duna A.K. Alenazi; Kholoud M. Alnahdi; Shareefa Ahmed Alshareef; Menier Al-Anazi; Nawaa Ali H. Alshammari; Maha Ali Aljowni; Raedah A.S. Alatawi; Abeer Abdulaziz H. Bukhari; Jawza Sh. Alnawmasi; Yasmeen G. Abou El-Reash; M. Monier; et al. (Journal of Water Process Engineering, 2025)

Electrolyzed water as a microbial control measure for white soft cheese - Salwa M. Awad; Eman F. Abdel-latif; Khalid Sh Tolba; Huda Elsayed; Zeinab I. Ali; Adel M. Saudi (International Dairy Journal, 2025)

Formulation and Characterization of Isavuconazole-Loaded Chitosan/Sodium Alginate Nanoparticles for Dermal Delivery: in Vitro and in Vivo Evaluation for Enhanced Antifungal Therapy - Shahzad Khan; Asif Nawaz; Muhammad Khursheed Alam Shah; Muhammad Shahid Latif; Muhammad Haroon; Abdullah Khan; Tarek Mohamed Ali Elsayed (Journal of Pharmaceutical Innovation, 2025)

Ameliorative potential of dietary supplements, ZnO-K, citrus essential oil, and pumpkin seed oil, on sperm quality in Nile tilapia: Insights from CASA, DNA integrity, antioxidant enzymes, and gene expressions - Marwa M. Ali; Kamal Fathy Elboray; Engy T. Megahed; Hany T. Abu-Taleb; Alshimaa E. Elsayed; Eman Y. Mohammady; Mona S. Amer; Soliman A. Morsi; Eman M. Abbas; Mohamed S. Hassaan; Hosam Elsaied (Fish Physiology and Biochemistry, 2025)
Improving sperm quality is essential for enhancing the reproductive efficiency of Oreochromis niloticus . This study evaluated the effect of three dietary antioxidant supplements, kaolinite-doped zinc oxide (ZnO-K), citrus essential oil (CEO), and pumpkin seed oil (PSO), on sperm quality parameters. A suite of integrative assessments, including Computer-Assisted Semen Analysis (CASA) parameters, spermatozoa DNA integrity, antioxidant enzyme assays, and gene expression profiling, was applied to validate sperm quality. A total of 192 adult males (mean weight 421.31 g ± 30.41 SD) were assigned to four dietary groups, each with three replicates. The control group received a basal diet without supplementation. The experimental groups were fed diets supplemented with ZnO-K (0.06 g kg⁻ 1 ), CEO (10 g kg⁻ 1 ), or PSO (15 g kg⁻ 1 ). ZnO-K supplementation significantly ( P < 0.05) increased milt volume (1.40 ± 0.10 ml) and sperm concentration (5.676 × 10 9 sperm ml −1 ), along with marked improvements in CASA parameters (sperm motility and velocity) and DNA integrity. Antioxidant enzymes, catalase, CAT, glutathione peroxidase, GPX, and superoxide dismutase, SOD, were also significantly elevated in the ZnO-K group, recording activity values of 47.333 ± 1.452 U ml −1 milt, 65.667 ± 5.547 mU ml −1 milt and 60.667 ± 3.382 U ml −1 milt, respectively. Gene expression analysis revealed that CEO induced the highest upregulation of HSP70 , while both CEO and ZnO-K significantly upregulated CC chemokine expression compared to control. In contrast, PSO consistently showed the lowest performance across all measured parameters. Collectively, ZnO-K supplementation most effectively enhanced sperm physiological and biochemical quality, whereas CEO predominantly supported cellular stress protection through gene expression modulation. These findings offered practical implications for optimizing artificial reproduction and sperm cryopreservation strategies in tilapia aquaculture.

Fatty acid profiles and differential genes expression in Tunisian olive cultivars: a study of fruit ripening and quality attributes - Sihem Ben Ali; Faiza Boussora; Mbarka Ben Mohamed; Tebra Triki; Leila Bennani; Abeer Hashem; Graciela Dolores Avila-Quezada; Elsayed Fathi Abd Allah; Naziha Grati Kammoun; Ferdaous Guasmi (Euro-Mediterranean Journal for Environmental Integration, 2025)

The Role of MicroRNAs in Neurodegeneration: Insights from Huntington’s Disease - Reda M. Mansour; Abanoub A. S. Shaker; Ahmed I. Abulsoud; Sherif S. Abdel Mageed; Alaa Ashraf; Elsayed G. E. Elsakka; Mohammed. I. Dahab; Mohamed M. Sadek; Farah A. Awad; Radwa H. Lutfy; Hanan Elimam; Ahmed H. I. Faraag; et al. (Molecular Neurobiology, 2025)

Projecting rice water footprint for different shared socioeconomic pathways under arid climate conditions - Elsayed Ahmed Elsadek; Diaa Eldin M. Elshikha; Ahmed Awad; Yousef Alhaj Hamoud; Ahmed Mohamed Elsheikha; Clinton Williams; Ethan Orr; Hiba Shaghaleh; Amar Ali Adam Hamad; Kelly R. Thorp; Ahmed Elbeltagi (Irrigation Science, 2025)

Allicin protects against pancreatic damage induced by zearalenone in rats by inhibiting endoplasmic reticulum stress - Amany Mohamed Shalaby; Amira Mostafa Elshamy; Abdulfatah Mohammed Albakkosh; Sulaiman Mohammed Alnasser; Mohammed Alorini; Fatima A. Jaber; Mohamed Ali Alabiad; Sabah Mohamed Hanafy; Nema Soliman; Shereen Elsayed Tawfeek (Tissue and Cell, 2025)

Behavioral and neurological responses of Oreochromis niloticus to chronic cyclic hypoxia: mechanistic insights into hypoxia-responsive genes, pro-inflammatory and apoptotic pathways: role of camel whey protein hydrolysate - Amany Abdel-Rahman Mohamed; Abdelwahab A. Abdelwarith; Elsayed M. Younis; Rowida E. Ibrahim; Tarek Khamis; Ali Osman; Mohamed M. M. Metwally; Abd Elhakeem El-Murr; Simon J. Davies; Yasmina M. Abd-Elhakim (Veterinary Research Communications, 2025)

Investigating the impact of camel whey protein hydrolysate on cyp1a1 and keap1/nrf2 expression in hypoxic stress-affected liver tissue of Oreochromis niloticus - Amany Abdel-Rahman Mohamed; Afaf A. Kishta; Elsayed M. Younis; Abdelwahab A. Abdelwarith; Yasmina M. Abd-Elhakim; Rowida E. Ibrahim; Mohamed M. M. Metwally; Tarek Khamis; Ali Osman; Simon J. Davies; Mohamed A. Elbealy (Journal of Comparative Physiology B, 2025)

The impact of betalains and organic selenium on the physiological responses, blood metabolites, redox status, and semen quality of heat-stressed rabbits - Tharwat A. Imbabi; Eman H. Halawa; Elsayed M. Younis; Abdel-Wahab A. Abdel-Warith; Dina A. Selim; Mohamed H. Abdel Aal; Lamiaa M.M. EL-Maghraby; Abdalla El-Hadary; Shimaa A. Amer; Simon J. Davies; Mohamed S. Basiouny; Mahmoud Sitohy; et al. (Animal Feed Science and Technology, 2025)

The potential of bone marrow derived mesenchymal stem cells in treating cisplatin induced sensorineural hearing loss in a guinea pig animal model - Mohamed Hassan Ali Elsayed Abdelwahed; Mohamed Hussien Badreldin; Ibrahim Hassan Ibrahim; Reham Farouk Zittoon; Rania A. Galhom; Sally S. Mohammed; Yehia Mohamed Ashry (Tissue and Cell, 2025)

Acetamiprid-induced pulmonary toxicity via oxidative stress, epithelial-mesenchymal transition, apoptosis, and extracellular matrix accumulation in human lung epithelial cells and fibroblasts: Protective role of heat-killed Lactobacilli - Samah S. Arafa; Heba A. Elnoury; Sahar Badr El-Din; Mohamed A. Sakr; Fatma Fawzi Hendawi; Rehab Ali Elsayed Masoud; Samia Soliman Barghash; Doaa Sabry Elbehairy; Ayat Abdelaty Hemeda; Islam Mostafa Farrag; Doaa Sayed Abdelrahman; Amira Mohammad Elsadek; et al. (Food and Chemical Toxicology, 2025)

Enhancing single-stage partial nitritation-anammox process with airlift inner-circulation and oxygen partition: A novel strategy for treating high-strength ammonium wastewater - Runchu Wei; Zhigang Tang; Sha Wu; Risen Yang; Hanbo Yu; Jing Chen; Jingyi Jiang; Jianhong Jiang; Zhe Kong; Yanxiao Wei; Ali E.A. Elsayed; Hong Chen (Environmental Research, 2025)

Alleviative potential of dietary essential oils against nickel toxicity triggers neurobehavioral abnormalities, biochemical dysfunction, and histopathological alterations in Nile tilapia - Shaimaa A. A. Ahmed; Ali Adel Ali Ahmed; Gehad E. Elshopakey; Elsayed M. Younis; Abdelwahab A. Abdelwarith; Mai Farag Saad; Simon J. Davies; Rowida E. Ibrahim; Asmaa Edrees (Veterinary Research Communications, 2025)

Carbonate alkalinity induces stress responses and renal and metabolic disorders in Nile tilapia: mitigation by camel whey protein hydrolysate diet - Rowida E. Ibrahim; Abdelwahab A. Abdelwarith; Elsayed M. Younis; Amany Abdel-Rahman Mohamed; Tarek Khamis; Ali Osman; Mohamed M. M. Metwally; Simon J. Davies; Yasmina M. Abd-Elhakim (Fish Physiology and Biochemistry, 2025)

Long-term in-situ performance of volcanic rock- and zeolite-based bioretention facilities for roof runoff purification: Pollutant removal, soil characteristics and microbial community dynamics - Shuanglin Yang; Yiyi Deng; Jingyi Jiang; Zhe Kong; Elsayed A.E. Ali; Ronghua Xu; Zhengyu Deng; Wang Jiang; Hong Chen (Journal of Water Process Engineering, 2025)

Malfunction diagnosis based on residence time distribution of radiotracer signals in industrial processes using machine learning techniques - Mohamed S. El_Tokhy; H. Kasban; Elsayed H. Ali (Annals of Nuclear Energy, 2025)

Potential of using kidney bean (Phaseolus vulgaris L) protein hydrolysate as a plant protein supplement in Nile tilapia (Oreochromis niloticus) diets: effects on growth, hematology, histology, and blood biochemical parameters - Shimaa A. Amer; Rowida E. Ibrahim; Elsayed M. Younis; Abdel-Wahab A. Abdel-Warith; Ali Osman; Simon J. Davies; Medhat S. Shakweer (Aquaculture International, 2025)

Bio-catalytic activity of novel poly(ethylene glycol) methacrylate hybridized silver nanomaterials - Natasha Anwar; Mohib Shah; Saad Haroon Anwar; Muhammad Ishaq Ali Shah; Amir Zada; Hammad Ahmad Jan; Abeer Hashem; Graciela Dolores Avila-Quezada; Elsayed Fathi Abd-Allah (South African Journal of Botany, 2025)

Administration of melatonin nanoparticles improves testicular blood flow, echotexture of testicular parenchyma, scrotal circumference, and levels of estradiol and nitric oxide in prepubertal ossimi rams under summer heat stress - Eman Fayez; Haney Samir; Fady Sayed Youssef; Ali Salama; Mohamed AI ElSayed (Veterinary Research Communications, 2024)
Environmental heat stress (HS) impairs reproductive efficiency in farm animals. This study investigated, for the first time, how the melatonin and melatonin nanoparticles treatment affected the testicular hemodynamics, testicular volume, echotexture [Pixel intensity (PIX) and integrated density (IND)], scrotal circumference, serum concentration of testosterone (T), estradiol (E 2 ), nitric oxide (NO), and total antioxidant capacity (TAC) in prepubertal Ossimi ram lambs in hot climatic conditions. The lambs undergoing examination had a temperature humidity index (THI) of 87.05 ± 1.70, indicating severe HS condition. Fifteen prepubertal Ossimi ram lambs were exposed to a single s.c injection of either nano melatonin (nano melatonin group; 20 mg/ram; n = 5) or melatonin suspended in two ml of corn oil (melatonin group; 40 mg/ram; n = 5) or two ml of corn oil (control group; n = 5). Blood collection and ultrasonographic assessment of the testes and supratesticular arteries (STAs) were conducted immediately before treatment (W0) and once weekly for six successive weeks after nano melatonin and melatonin injection (W1-W6). Results revealed decreases ( P < 0.05) in the Doppler indices (resistive index; RI and pulsatility index; PI) of the testicular arteries at most time points of the study in the nano melatonin and melatonin groups. PIX of testicular parenchyma was significantly increased (P ˂ 0.05) in the treated groups compared to the control one. IND of testicular parenchyma increased significantly in the nano melatonin group compared to the melatonin and control groups. Testicular volume and scrotal circumference significantly increased ( P < 0.05) in nano melatonin and melatonin groups compared to the control one. T concentration did not significantly ( P > 0.05) change in the treated groups compared to the control group. E 2 , NO, and TAC concentrations increased ( P < 0.05) in the treated groups compared to the control one. In conclusion, this study extrapolated that administrations of melatonin or nano melatonin can ameliorate the effects of environmental HS in prepubertal Ossimi ram lambs with a more protective effect and lower dose of nano melatonin.

Effects of dietary Arthrospira platensis phycocyanin on growth, fatty acid assessment of breast muscles, hematobiochemical, immunological responses, and hepatic histomorphology in broiler chickens - Shimaa A. Amer; Amany Behairy; Amr A. Moustafa; Azhar Eltanahy; Elsayed M. Younis; Abdel-Wahab A. Abdel-Warith; Ali Osman; Ahmed Gouda; Simon J. Davies; Samar A. Tolba (Journal of Applied Phycology, 2024)

Camel whey protein hydrolysate diet mitigates alkaline stress–induced biochemical disorders and restores the target of rapamycin, MAPK pathway, and autophagy-related gene expression in Nile tilapia - Rowida E. Ibrahim; Gehad E. Elshopakey; Mohamed Y. M. Aly; Abdelwahab A. Abdelwarith; Elsayed M. Younis; Yasmina M. Abd-Elhakim; Tarek Khamis; Ali Osman; Mohamed M. M. Metwally; Simon J. Davies; Amany Abdel-Rahman Mohamed (Aquaculture International, 2024)

Using moringa (Moringa oleifera) seed protein hydrolysate as a dietary protein supplement modulates hemato-biochemical indices, antioxidant response, and tissue histo-morphology of Nile tilapia (Oreochromis niloticus) - Rowida E. Ibrahim; Shimaa A. Amer; Nasreddin R. Rhouma; Elsayed M. Younis; Abdelwahab A. Abdelwarith; Heba M. Abdel-Ghany; Gehad E. Elshobaky; Mahmoud M. El-Saber; Ali Osman; Simon J. Davies; Afaf N. Abdel Rahman (Aquaculture International, 2024)

Evaluation of asphalt mixtures modified with polyethylene terephthalate (PET) - Elsayed Adel Fahmy; Ahmed Mohammed Youssef; Esraa Emam Ali; Ahmed Algabry; Omar Elbagalati (Innovative Infrastructure Solutions, 2024)
Polyethylene terephthalate (PET) waste, ubiquitous in packaging and shipping industries, offers logistical advantages through its lightweight, durable nature, fostering cost-effective transportation. However, concerns over PET’s environmental impact arise from its persistence in ecosystems and contribution to pollution, urging industries to prioritize responsible waste management and recycling strategies. Recognizing the pivotal role of the construction industry, leveraging PET recycling in asphalt mixtures presents an applicable solution to curtail the environmental footprint of PET waste. Roadway asphalt construction, a significant industry, holds substantial potential to integrate PET waste into asphalt, offering a promising avenue for sustainable waste utilization. This research investigates the integration of PET waste into Egyptian asphalt mixtures across nine distinct compositions, varying binder percentages (3.0%, 3.50%, and 4%) and PET ratios (6%, 7%, and 8%). Marshall and Hamburg Wheel Rutting tests were conducted, comparing these formulations against a control mix devoid of PET. Notably, optimal outcomes emerged from the 3% binder with 8% PET combination, exhibiting enhanced mix stability and stiffness while meeting established mix design standards, signifying promising improvements in sustainability without compromising performance metrics.

Efficient adsorption of fluorescein dye from aqueous solutions by Al/Th-MOF bimetal-organic frameworks: Adsorption isotherm, kinetics, DFT computation, and optimization via Box-Behnken design - Nawaa Ali H. Alshammari; Jawza Sh Alnawmasi; Alya M. Alotaibi; Odeh A.O. Alshammari; May Abdullah Abomuti; Nadia H. Elsayed; Ashraf A. El-Bindary (Process Safety and Environmental Protection, 2024)

Genotype classification and pathogenicity of infectious bursal disease virus circulating in vaccinated broiler chicken farms - Samah M. Mosad; Mona M. Elsayed; Enas M. Hammad; Basma M. Hendam; Hanaa S. Ali; Abdelfattah H. Eladl; Mohamed A. Saif (Veterinary Research Communications, 2024)
This study investigated the genotype classification and pathogenicity of infectious bursal disease virus (IBDV) circulating in vaccinated broiler chicken farms in Egypt. A total of 150 samples were collected from 30 vaccinated commercial broiler chicken farms and pooled into 30 working samples. IBDV was tested using reverse transcriptase polymerase chain reaction (RT-PCR) amplification of the hypervariable region of the viral protein 2 (hvVP2) and the VP1 gene 5’ extremity. Both RT-PCR fragments were sequenced from six samples, and then the obtained nucleotide sequences were analyzed. The IBDV genotypes were identified using nucleotide sequences. Five sequences of the six strains examined were classified as genotype A3B2 for the highly virulent segments A and B (vv-A/vv-B IBDV). Interestingly, this study identified and classified a novel segment-reassortant strain as the A1B2 genotype. Specifically, it involved the segment reassortment of classical virulent segment A (cv-A) with vv-B producing cv-A/vv-B reassortant IBDV. Subsequently, we compared the pathogenicity of reassortant (cv-A/vv-B) IBDV and vvIBDV strains identified in this study. Both strains developed typical IBD clinical signs, postmortem lesions, histopathology, immunohistochemistry, and lesion scores, which were more severe in vvIBDV than reassortant IBDV. In conclusion, this is the first report of the genotype classification based on both genome segments (hvVP2 and VP1) with pathogenicity of IBDV circulating in vaccinated broiler chicken farms and this pathogenicity is more severe in vvIBDV strain than a novel reassortant IBDV strain.

Angiotensin II Type 1 receptor blockade attenuates the neuropathological changes in the spinal cords of diabetic rats with modulation of nuclear factor erythroid 2-related factor 2/ heme oxygenase 1 system - Hassan Reda Hassan Elsayed; Eyad Mohamed Tolba Ali; Mohammed Rami Rabei; Eman Mohamad El Nashar; Mansour Abdullah Alghamdi; Norah Saeed Al-Zahrani; Shaker Hassan Alshehri; Rashid A. Aldahhan; Amira Ibrahim Morsy (Tissue and Cell, 2024)

Effect of intermittent fasting on adriamycin-induced nephropathy: Possible underlying mechanisms - Fathy H. Elsaid; Abdelaziz M. Hussein; Elsayed A. Eid; Omar A. Ammar; Ali Ali Khalil (Tissue and Cell, 2024)

The Role of RIN3 Gene in Alzheimer’s Disease Pathogenesis: a Comprehensive Review - Mostafa Meshref; Hazem S. Ghaith; Mohamed Ahmed Hammad; Mahmoud Mohamed Mohamed Shalaby; Faris Ayasra; Fatma Ahmed Monib; Mohamed S. Attia; Mahmoud A. Ebada; Hanaa Elsayed; Ali Shalash; Eshak I. Bahbah (Molecular Neurobiology, 2024)
Alzheimer’s disease (AD) is a globally prevalent form of dementia that impacts diverse populations and is characterized by progressive neurodegeneration and impairments in executive memory. Although the exact mechanisms underlying AD pathogenesis remain unclear, it is commonly accepted that the aggregation of misfolded proteins, such as amyloid plaques and neurofibrillary tau tangles, plays a critical role. Additionally, AD is a multifactorial condition influenced by various genetic factors and can manifest as either early-onset AD (EOAD) or late-onset AD (LOAD), each associated with specific gene variants. One gene of particular interest in both EOAD and LOAD is RIN3, a guanine nucleotide exchange factor. This gene plays a multifaceted role in AD pathogenesis. Firstly, upregulation of RIN3 can result in endosomal enlargement and dysfunction, thereby facilitating the accumulation of beta-amyloid (Aβ) peptides in the brain. Secondly, RIN3 has been shown to impact the PICLAM pathway, affecting transcytosis across the blood-brain barrier. Lastly, RIN3 has implications for immune-mediated responses, notably through its influence on the PTK2B gene. This review aims to provide a concise overview of AD and delve into the role of the RIN3 gene in its pathogenesis.

Insights into enhanced pollutant removal from road runoff by functional microorganisms in a field-scale bioretention facility - Chuncai Zhang; Xin Luo; Yiyi Deng; Zhengyu Deng; Ronghua Xu; Mariam A. Amer; Elsayed A.E. Ali; Jingyi Jiang; Hong Chen (Journal of Water Process Engineering, 2024)

Evaluating the impact of artificial maturation on the petrophysical and geochemical properties of unconventional shale formations by integrating dielectric and NMR measurements - Amjed Hassan; Mahmoud Elsayed; Ali Oshaish; Salah Al-Ofi; Ammar El-Husseiny; Israa S. Abu-Mahfouz; Mohamed Mahmoud; Mohamed Abouelresh; Hussein Attia (International Journal of Coal Geology, 2024)

From source to house: unraveling the seasonal effect of water distribution system on drinking water quality of poultry farms under Egyptian environmental condition - Mohammed Abdelhameed Kamal; Rashed A. Alhotan; Ali R. Al Sulaiman; Elsayed Osman Hussein; Branislav Galik; Ahmed Ali Saleh (Environmental Science and Pollution Research, 2024)

Use of moringa protein hydrolysate as a fishmeal replacer in diet of Oreochromis niloticus: Effects on growth, digestive enzymes, protein transporters and immune status - Shimaa A. Amer; Afaf N. Abdel Rahman; Mohamed ElHady; Ali Osman; Elsayed M. Younis; Abdel-Wahab A. Abdel-Warith; Amr A. Moustafa; Tarek Khamis; Simon J. Davies; Rowida E. Ibrahim (Aquaculture, 2024)

Roof runoff pollution control with operating time based on a field-scale assembled bioretention facility: Performance and microbial community dynamics - Shuanglin Yang; Xiaokang Su; Yong Jiang; Yiyi Deng; Zhengyu Deng; Xin Luo; Jing Chen; Jingyi Jiang; Lei Zhu; Ronghua Xu; Guina Luo; Mariam A. Amer; et al. (Journal of Water Process Engineering, 2024)

Evaluation and performance comparison of different models for global solar radiation forecasting: a case study on five cities - Mohamed A. Ali; Ashraf Elsayed; Islam Elkabani; M. Elsayed Youssef; Gasser E. Hassan (Environment, Development and Sustainability, 2023)
Recently, solar energy has emerged as the most promising renewable energy source to meet the world’s energy demands. However, to harness the potential of solar energy, accurate data on solar radiation are crucial. It is considered the first step in assessing solar resources for various applications and achieving energy sustainability goals. Due to the unavailability of solar radiation measurements in many parts of the world, several models have been developed to predict global solar radiation (GSR) at these locations. Thus, this study aims to evaluate the proficiency of several GSR models at five new locations and determine the most suitable one for GSR prediction. The study has further developed solar radiation models for these new locations, as well as general ones for the entire region, which does not have any GSR models despite the existence of many planned solar energy facilities in this area. Additionally, the study investigates the effect of changing the length of the validation dataset on models’ performance and accuracy, as well as assesses the introduced models’ generalization capability. To achieve these objectives, the observed data of GSR for approximately 37 years at studied locations are used to develop and validate the proposed models. The study’s findings reveal that Model 1 provides the best performance at all locations, with accuracy, coefficient of determination ( $$R^{2}$$ R 2 ), ranging from 95 to 98%, except for the coastal location, where it is from 91 to 95%. The remaining performance indicators of the best models, such as RMSE, MABE, MAPE, and $$r$$ r , are good, and their values range from 0.7863 to 1.9097 (MJ m −2 day −1 ), from 0.6430 to 1.7060 (MJ m −2 day −1 ), from 3.4319 to 10.0890 (%), and from 0.9914 to 0.9981, respectively. The length of the validation dataset has a slight effect on the models’ performance, ranging from about 1% to 2%. Therefore, Model 1 is the recommended solar radiation model, which can provide precise and rapid estimates of global solar radiation. This approach could be used in the design and performance evaluation of many solar applications. The primary benefit of this approach in the current investigation is that temperature data are continuously and effortlessly recorded for various purposes.

Towards achieving university sustainability! Linking social responsibility with knowledge sharing in Saudi universities - Afroze Nazneen; Islam Elgammal; Zubair Rashid Khan; Muhammad Haroon Shoukat; Ali Elsayed Shehata; Kareem M. Selem (Journal of Cleaner Production, 2023)

Kidney bean protein hydrolysate as a fish meal replacer: Effects on growth, digestive enzymes, metabolic functions, immune-antioxidant parameters and their related gene expression, intestinal and muscular gene expression - Rowida E. Ibrahim; Samar A. Tolba; Elsayed M. Younis; Abdel-Wahab A. Abdel-Warith; Shimaa I. Shalaby; Ali Osman; Tarek Khamis; Mohamed A. Eissa; Simon J. Davies; Shimaa A. Amer (Aquaculture, 2023)

Valorization of lignocellulosic wastes for sustainable xylanase production from locally isolated Bacillus subtilis exploited for xylooligosaccharides’ production with potential antimicrobial activity - Hamada El-Gendi; Ahmed S. Badawy; Elsayed K. Bakhiet; Mohammed Rawway; Salah G. Ali (Archives of Microbiology, 2023)
The worldwide availability of lignocellulosic wastes represents a serious environmental challenge with potential opportunities. Xylanases are crucial in lignocellulosic bio-hydrolysis, but the low enzyme productivity and stability are still challenges. In the current study, Bacillus subtilis (coded ARSE2) revealed potent xylanase activity among other local isolates. The enzyme production optimization revealed that maximum enzyme production (490.58 U/mL) was achieved with 1% xylan, 1.4% peptone, and 5% NaCl at 30 °C and pH 9. Furthermore, several lignocellulosic wastes were exploited for sustainable xylanase production, where sugarcane bagasse (16%) under solid-state fermentation and woody sawdust (2%) under submerged fermentation supported the maximum enzyme titer of about 472.03 and 485.7 U/mL, respectively. The partially purified enzyme revealed two protein bands at 42 and 30 kDa. The partially purified enzyme revealed remarkable enzyme activity and stability at 50–60 °C and pH 8–9. The enzyme also revealed significant stability toward tween-80, urea, DTT, and EDTA with V max and K m values of 1481.5 U/mL and 0.187 mM, respectively. Additionally, the purified xylanase was applied for xylooligosaccharides production, which revealed significant antimicrobial activity toward Staphylococcus aureus with lower activity against Escherichia coli . Hence, the locally isolated Bacillus subtilis ARSE2 could fulfill the xylanase production requirements in terms of economic production at a high titer with promising enzyme characteristics. Additionally, the resultant xylooligosaccharides revealed a promising antimicrobial potential, which paves the way for other medical applications.

Neem seed protein hydrolysate as a fishmeal substitute in Nile tilapia: Effects on antioxidant/immune pathway, growth, amino acid transporters-related gene expression, and Aeromonas veronii resistance - Afaf N. Abdel Rahman; Shimaa A. Amer; Shimaa R. Masoud; Mahmoud M. El-Saber; Ali Osman; Elsayed M. Younis; Abdelwahab A. Abdelwarith; Simon J. Davies; Tarek Khamis; Rowida E. Ibrahim (Aquaculture, 2023)

Principal component analysis of phenolic compounds of grape waste parts and correlations to their bioassays - Salma Ahmed El-Sawi; Nermin Ahmed Ragab; Amany Ameen Sleem; Ayman Ali Farghaly; Ghada Elsayed Ahmed Awad; Maii Abdelnaby Ismail Maamoun (Biocatalysis and Agricultural Biotechnology, 2023)

Development of high-resolution gridded data for water availability identification through GRACE data downscaling: Development of machine learning models - Hai Tao; Ahmed H. Al-Sulttani; Sinan Q. Salih; Mustafa K.A. Mohammed; Mohammad Amir Khan; Beste Hamiye Beyaztas; Mumtaz Ali; Salah Elsayed; Shamsuddin Shahid; Zaher Mundher Yaseen (Atmospheric Research, 2023)

Hospital and laboratory outcomes of patients with COVID-19 who received vitamin D supplementation: a systematic review and meta-analysis of randomized controlled trials - Mohamed Sayed Zaazouee; Mahmoud Eleisawy; Amira M. Abdalalaziz; Mahmoud M. Elhady; Omar Adel Ali; Taghreed Mohamed Abdelbari; Sara Mohamed Hasan; Hossam Waleed Almadhoon; Alaa Yehia Ahmed; Alaa Shaban Fassad; Rewan Elgendy; Eman Adnan Abdel-Baset; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)
Coronavirus disease 2019 (COVID-19) has a wide-ranging spectrum of clinical symptoms, from asymptomatic/mild to severe. Recent research indicates that, among several factors, a low vitamin D level is a modifiable risk factor for COVID-19 patients. This study aims to evaluate the effect of vitamin D on hospital and laboratory outcomes of patients with COVID-19. Five databases (PubMed, Embase, Scopus, Web of Science, and Cochrane Library) and clinicaltrials.gov were searched until July 2022, using relevant keywords/Mesh terms. Only randomized clinical trials (RCTs) that addressed the topic were included. The Cochrane tool was used to assess the studies’ risk of bias, and the data were analyzed using the review manager (RevMan 5.4). We included nine RCTs with 1586 confirmed COVID-19 patients. Vitamin D group showed a significant reduction of intensive care unit (ICU) admission (risk ratio = 0.59, 95% confidence interval (CI) [0.41, 0.84], P = 0.003), and higher change in vitamin D level (standardized mean difference = 2.27, 95% CI [2.08, 2.47], P < 0.00001) compared to the control group. Other studied hospital and laboratory outcomes showed non-significant difference between vitamin D and the control group ( P ≥ 0.05). In conclusion, vitamin D reduced the risk of ICU admission and showed superiority in changing vitamin D level compared to the control group. However, other outcomes showed no difference between the two groups. More RCTs are needed to confirm these results.

Correction to: The protective role of iodine and MS‑222 against stress response and bacterial infections during Nile tilapia (Oreochromis niloticus) transportation - Ahmed H. Sherif; Elsayed A. Eldessouki; Nader M. Sabry; Nadia G. Ali (Aquaculture International, 2023)

Path toward sustainable desalination: Sodium precipitation and carbon capture - Ahmed Elsayed; Ali H. Al-Marzouqi (Desalination, 2023)

Delineation of hydrothermal alteration zones associated with mineral deposits, using remote sensing and airborne geophysics data. A case study: El-Bakriya area, Central Eastern Desert, Egypt - Reda Abdu Yousef El-Qassas; Atef Mohamed Abu-Donia; Ali Elsayed Ali Omar (Acta Geodaetica et Geophysica, 2023)
El-Bakriya area is situated in the Central Eastern Desert of Egypt. It includes several mineral occurrences and/or deposits. Data from remote sensing and airborne geophysics (gamma-ray and magnetic) were combined to identify the hydrothermal alteration zones and structures related to these occurrences. Various processing of ASTER satellite images revealed fifteen zones of high probability for metallic mineralizations. Airborne gamma-ray spectrometric data clarify K-enrichment zones, which are correlated geologically with the distribution of calc-alkaline, alkali feldspar granites (Younger granites), and calc-alkaline quartzdiorites to granodiorites (Older granites), as well as basement metavolcanics and metasediments. An integrated hydrothermal alteration map was constructed, based on both ASTER remote sensing and airborne gamma-ray spectrometric data. This map delineates some metallic mineral occurrences and/or deposits, which are located in the detected hydrothermal alteration zones. Besides, it displays new potential zones for mineralization, such as: Gabal (G.) El-Shalul, G. El-Bakriya, G. Siwat El-Arsha and G. Umm Bisilla. The geologic and airborne magnetic maps demonstrate five structural lineament trends of E–W, ENE–WSW, NE–SW, NW–SE, and NNW–SSE directions, which might act as pathways to transport the hydrothermal solutions in the study area.

Litoarbolide A: an undescribed sesquiterpenoid from the Red Sea soft coral Litophyton arboreum with an in vitro anti-malarial activity evaluation - Mohammed M. A. Ahmed; Ehab A. Ragab; Ahmed Zayed; Elsayed M. El-Ghaly; Said K. Ismail; Shabana I. Khan; Zulfiqar Ali; Amar G. Chittiboyina; Ikhlas A. Khan (Natural Product Research, 2023)

Clarithromycin-, and metronidazole-resistant Helicobacter pylori isolated from raw and ready-to-eat meat in Mansoura, Egypt - Aya Elsayed Maghrabia; Hend Ali Elshebrawy; Mahmoud Ahmed Mahros; Mohammed Mohammed Elgazzar; Khalid Ibrahim Sallam (International Journal of Food Microbiology, 2023)

The protective role of iodine and MS-222 against stress response and bacterial infections during Nile tilapia (Oreochromis niloticus) transportation - Ahmed H. Sherif; Elsayed A. Eldessouki; Nader M. Sabry; Nadia G. Ali (Aquaculture International, 2023)
Fish transportation is a regular farming and experimental practice that mainly results in stress conditions that may extend to induce a high mortality rate. In the present experimental simulation, Oreochromis niloticus were transported for 2 h and maintained for another 6 h in transportation containers to assess the effect of tranquilization with tricaine methanesulfonate (MS-222) and/or the addition of iodine on mortality rate and restoring the normal physiological functions. Experimental fish were divided into four groups: group 1 (control) was transported in farm water without MS-222 or iodine, group (2) was transported in farm water supplemented with 40 mg/L of MS-222, fish in group (3) were transported in farm water supplemented with 40 mg/L of MS-222 + 10 ppm iodine, and fish in group (4) were transported in farm water containing 10 ppm iodine. Blood samples were collected for the determination of serum cortisol and glucose, while skin mucus was collected for assaying lysozyme, peroxidase and antibacterial activity; cumulative mortality rate; and food reflexes which were assessed at 0 h, 1 h, 6 h, 48 h, 7 days and 14 days post 2 h transportation. The results indicated that fish tranquilization with MS-222 and/or treatment with iodine mitigated the stress condition associated with transportation and accelerate restoration of the normal physiological and immunological status. So, it was recommended to use the MS-222 as a tranquillizer together with iodine as an antiseptic during transportation of O. niloticus .

Co-digestion of cow manure and food waste for biogas enhancement and nutrients revival in bio-circular economy - Yasir Abbas; Sining Yun; Ayaz Mehmood; Fayyaz Ali Shah; Kaijun Wang; Elsayed Tag Eldin; Wahidah H. Al-Qahtani; Shafaqat Ali; Patrizia Bocchetta (Chemosphere, 2023)

The quest for negative electrode materials for Supercapacitors: 2D materials as a promising family - Muhammad Sufyan Javed; Abdul Mateen; Iftikhar Hussain; Salamat Ali; Sumreen Asim; Awais Ahmad; Elsayed tag Eldin; Majed A. Bajaber; Tayyaba Najam; Weihua Han (Chemical Engineering Journal, 2023)

Ni-alginate hydrogel beads for establishing breakthrough curves of lead ions removal from aqueous solutions - Nesreen M. Sami; A. A. Elsayed; M. M. S. Ali; Sayed S. Metwally (Environmental Science and Pollution Research, 2022)
The scientific impact of this work is the protection of the environment from hazardous pollutants using a column technique. Besides its higher stability at working pH and its time persisting, Ni-alginate has a higher ability to remove lead ions compared to the other prepared beads (Sr-alginate, Co-alginate, and Ca-alginate). Also, Ni-alginate possessed a higher removal percent, 93.3%, toward Pb 2+ than the other ions, taking the sorption order of Pb 2+ > Sr 2+ > Co 2+ > Cd 2+ > Zn 2+ . Therefore, this study focused on using Ni-alginate as a selective sorbent for lead ions. Fixed-bed column was employed for the sorption process. The results for that efficiency are presented as breakthrough curves in view of the impact of various parameters; influent flow rate (1.5, 3.0, and 5.0 mL/min), lead concentration (100, 150, and 200 mg/L), and bed depth of sorbent (3.0, 5.0, and 7.0 cm). Breakthrough modeling including Thomas and Yan models was employed. The outcomes indicated that Thomas theory is more applicable. The overall outcomes indicated that Ni-alginate is recommended for selective removal of Pb 2+ from waste solutions.

Environmental Assessment of Potentially Toxic Elements Using Pollution Indices and Data-Driven Modeling in Surface Sediment of the Littoral Shelf of the Mediterranean Sea Coast and Gamasa Estuary, Egypt - Magda M. Abou El-Safa; Salah Elsayed; Osama Elsherbiny; Adel H. Elmetwalli; Mohamed Gad; Farahat S. Moghanm; Ebrahem M. Eid; Mostafa A. Taher; Mohamed H. E. El-Morsy; Hanan E. M. Osman; Ali H. Saleh (Journal of Marine Science and Engineering, 2022)
Coastal environmental assessment techniques have evolved into one of the most important fields for the long-term development and management of coastal zones. So, the overall aim of the present investigation was to provide effective approaches for making informed decisions about the Gamasa coast sediment quality. Over a two-year investigation, sediment samples were meticulously collected from the Gamasa estuary and littoral shelf. The inductively coupled plasma mass spectra (ICP-MS) was used to the total concentrations of Al, Fe, Ti, Mg, Mn, Cu, P, V, Ba, Cr, Sr, Co, Ni, Zn, Pb, Zr, and Ce. Single elements environmental pollution indices including the geoaccumulation index (Igeo), contamination factor (CF), and enrichment factor (EF), as well as multi-elements pollution indices comprising the potential ecological risk index (RI), degree of contamination (Dc), and pollution load index (PLI) were used to assess the sediment and the various geo-environmental variables affecting the Mediterranean coastal system. Furthermore, the Dc, PLI, and RI were estimated using the random forest (RF) and Back-Propagation Neural Network (BPNN) depending on the selected elements. According to the Dc results, all the investigated sediment samples categories were considerably contaminated. Cr, Co, Ni, Cu, Zr, V, Zn, P, and Mn showed remarkable enrichment in sediment samples and were originated from anthropogenic sources based on the CF, EF, and Igeo data. Moreover, the RI findings revealed that all the samples tested pose a low ecologically risk. Meanwhile, based on PLI, 70% of the Gamasa estuary samples were polluted, while 93.75% of littoral shelf sediment was unpolluted. The BPNNs -PCs-CD-17 model performed the best and demonstrated a better association between exceptional qualities and CD. With R2 values of 1.00 for calibration (Cal.) and 1.00 for validation (Val.). The BPNNs -PCs-PLI-17 models performed the best in terms of measuring PLI with respective R2 values of 1.00 and 0.98 for the Cal. and Val. datasets. The findings showed that the RF and BPNN models may be used to precisely quantify the pollution indices (Dc, PLI, and RI) in calibration (Cal.) and validation (Val.) datasets utilizing potentially toxic elements of surface sediment.

Sarcoroseolides A-D, four undescribed cembranoids from the Red Sea soft coral Sarcophyton roseum - Mohammed M. A. Ahmed; Mohamed A. Albadry; Ehab A. Ragab; Elsayed M. El-Ghaly; Said K. Ismail; Zulfiqar Ali; Shabana I. Khan; Amar G. Chittiboyina; Ikhlas A. Khan (Natural Product Research, 2022)

Environmental Pollution Indices and Multivariate Modeling Approaches for Assessing the Potentially Harmful Elements in Bottom Sediments of Qaroun Lake, Egypt - Ali H. Saleh; Mohamed Gad; Moataz M. Khalifa; Salah Elsayed; Farahat S. Moghanm; Adel M. Ghoneim; Subhan Danish; Rahul Datta; Moustapha E. Moustapha; Magda M. Abou El-Safa (Journal of Marine Science and Engineering, 2021)
This research intends to offer a scientific foundation for environmental monitoring and early warning which will aid in the environmental protection management of Qaroun Lake. Qaroun Lake is increasingly influenced by untreated wastewater discharge from many anthropogenic activities, making it vulnerable to pollution. For that, six environmental pollution indices, namely contamination factor (Cf), enrichment factor (EF), geo-accumulation index (Igeo), degree of contamination (Dc), pollution load index (PLI), and potential ecological risk index (RI), were utilized to assess the bottom sediment and to determine the different geo-environmental variables affecting the lake system. Cluster analysis (CA), and principal component analysis (PCA) were used to explore the potential pollution sources of heavy metal. Moreover, the efficiency of partial least-square regression (PLSR) and multiple linear regression (MLR) were tested to assess the Dc, PLI, and RI depending on the selected elements. The sediment samples were carefully collected from 16 locations of Qaroun Lake in two investigated years in 2018 and 2019. Total concentrations of Al, As, Ba, Cd, Co, Cr, Cu, Fe, Ga, Hf, Li, Mg, Mn, Mo, Ni, P, Pb, Sb, Se, Zn, and Zr were quantified using inductively coupled plasma mass spectra (ICP-MS). According to the Cf, EF, and Igeo results, As, Cd, Ga, Hf, P, Sb, Se, and Zr demonstrated significant enrichment in sediment and were derived from anthropogenic sources. According to Dc results, all collected samples were categorized under a very high degree of contamination. Further, the results of RI showed that the lake is at very high ecological risk. Meanwhile, the PLI data indicated 59% of lake was polluted and 41% had PLI

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Two-stage cultivation of Chlorella vulgaris using light and salt stress conditions for simultaneous production of lipid, carotenoids, and antioxidants - Hamdy Elsayed Ahmed Ali; Eman A. El-fayoumy; Wessam E. Rasmy; Ramadan M. Soliman; Mohd Azmuddin Abdullah (Journal of Applied Phycology, 2021)

The utility of electrocardiography and echocardiography in copper deficiency-induced cardiac damage in goats - Ahmed S. Mandour; Roushdy F. Elsayed; Asmaa O. Ali; Ahmed E. Mahmoud; Haney Samir; Amina A. Dessouki; Katsuhiro Matsuura; Izumi Watanabe; Kazuaki Sasaki; Salim Al-Rejaie; Tomohiko Yoshida; Kazumi Shimada; et al. (Environmental Science and Pollution Research, 2021)

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Improvement of the sorption behavior of aluminum silicate composite toward 134Cs and 60Co radionuclides by non-living biomass of Chlorella vulgaris - Gehan Abdel Rahman Dakroury; Shereen Fathy Abo-Zahra; Hisham Soliman Hassan; Hamdy Elsayed Ahmed Ali (Environmental Science and Pollution Research, 2020)

Impact of Soil Biochar Incorporation on the Uptake of Heavy Metals Present in Wastewater by Spinach Plants - Christopher Nzediegwu; Shiv Prasher; Eman Elsayed; Jaskaran Dhiman; Ali Mawof; Ramanbhai Patel (Water, Air, & Soil Pollution, 2020)

Propagation of the Multi-Scalar Aggregative Standardized Precipitation Temperature Index and its Application - Zulfiqar Ali; Ijaz Hussain; Muhammad Faisal; Dost Muhammad Khan; Rizwan Niaz; Elsayed Elsherbini Elashkar; Alaa Mohamd Shoukry (Water Resources Management, 2020)

An ensemble procedure for pattern recognition of regional drought - Zulfiqar Ali; Ijaz Hussain; Muhammad Faisal; Muhammad Yousuf Shad; Elsayed E. Elashkar; Showkat Gani (International Journal of Climatology, 2020)
Drought being a complex natural hazard is challenging to monitor. Although standardized procedures for drought characterization are commonly used, the uncertainty about accurate drought characterization under various procedures always exists. Therefore, for effective drought mitigation policies, it is necessary to compare the performance of new and the existing drought procedures. In this study, we proposed a new procedure— The Drought Intensity Pattern Determinate (DIPD) to examine and compare the spatial‐temporal intensities of various drought episodes based on Standardized Drought Indices (SDI). The DIPD framework provides a new tool— The Drought Concentration Index ( DCI ) to understand the annual intensity of drought classes by alluding the observed frequencies of drought episodes. At the preliminary level of assessment, DIPD is employed at 52 meteorological stations of Pakistan, and compared three commonly used standardized drought indices: Standardized Precipitation Index (SPI), Standardized Evapotranspiration Index (SPEI) and Standardized Precipitation Temperature Index (SPTI). Exploratory analysis shows a mixed picture as all the drought indices behaving similar for some patterns of drought classes, while some classes show significant discrepancies. In addition, we assessed and compared the spatial distributions using spatial Poisson lognormal model by assuming SDI as a non‐Gaussian process for individual total classes of observed DCI. Results show that the proposed method has ability to incorporate the inner variability in patterns of drought classes. In summary, the DIPD provided a new regional based comparative framework, which accounts the all possible episodes of drought classes and effect of inner discrepancies among quantitative values of SDI.

Effect of Biochar on the Yield of Potatoes Cultivated Under Wastewater Irrigation for Two Seasons - Christopher Nzediegwu; Shiv Prasher; Eman Elsayed; Jaskaran Dhiman; Ali Mawof; Ramanbhai Patel (Journal of Soil Science and Plant Nutrition, 2019)

The Ameliorative Role of 5-Aminolevulinic Acid (ALA) Under Cr Stress in Two Maize Cultivars Showing Differential Sensitivity to Cr Stress Tolerance - Ume Habiba; Shafaqat Ali; Muhammad Rizwan; Muhammad Bilal Hussain; Afzal Hussain; Pravej Alam; Abdulaziz A. Alqarawi; Abeer Hashem; Elsayed Fathi AbdAllah (Journal of Plant Growth Regulation, 2019)

The rapid detection and differentiation of Mycobacterium tuberculosis complex members from cattle and water buffaloes in the delta area of Egypt, using a combination of real-time and conventional PCR - Mohamed Sabry Abd Elraheam Elsayed; Ali Amer (Molecular Biology Reports, 2019)

Combined use of biochar and zinc oxide nanoparticle foliar spray improved the plant growth and decreased the cadmium accumulation in rice (Oryza sativa L.) plant - Shafaqat Ali; Muhammad Rizwan; Shamaila Noureen; Sarwat Anwar; Basharat Ali; Muhammad Naveed; Elsayed Fathi Abd_Allah; Abdulaziz A. Alqarawi; Parvaiz Ahmad (Environmental Science and Pollution Research, 2019)

Fulvic Acid Prevents Chromium-induced Morphological, Photosynthetic, and Oxidative Alterations in Wheat Irrigated with Tannery Waste Water - Shafaqat Ali; Muhammad Rizwan; Abdul Waqas; Muhammad Bilal Hussain; Afzal Hussain; Shiliang Liu; Abdulaziz A. Alqarawi; Abeer Hashem; Elsayed Fathi Abd_Allah (Journal of Plant Growth Regulation, 2018)

Paleoclimatic evolution of central Sudan during the Late Miocene to Pleistocene - Abdelgadir A. I. El Shafie; Khalid A. Elsayed Zeinelabdein; Ali A. M. Eisawi (Arabian Journal of Geosciences, 2013)